Studies On Adsorption Of Thionine Dye From It’s Aqueous Solution Over Low Cost Biosorbents - Saini, Alpana (My University, 2013)
Pollution of water is due to the presence of colorants. It is a severe socio-environmental problem caused by the discharge of industrial wastewater. In view of their toxicity, non-biodegradability and persistent nature, their removal becomes an absolute necessity. The aim of the present study is to remove Thionine dye from aqueous solution using peanut hull and walnut hull, under optimized conditions. The concentration of dyes, amount of adsorbent and agitation time was optimized over different biosorbents. Natural Walnut Hull was found to show better dye removal efficiency than the Peanut hull. The removal efficiency increased with increasing the Peanut Hull concentration significantly and reached a value as high as 91.3% at lower concentrations (up to 10 mg/L) there as no significant change was observed at higher concentrations, on the other hand the removal efficiency reached 100% in case of walnut hull. Spectrophotometric technique was adopted for the measurement of concentration of dyes before and after adsorption. The adsorption data was fitted to various kinetic Models and various adsorption isotherm equations. The characterization of adsorbent was done by using Scanning Electron Microscopy (SEM) in order to study the surface morphology. Fourier transform infrared (FT-IR) was done to study the bands which gives indication about the functional groups responsible for dye biosorption.
MT, CHED
Keywords: Biosorbents, adsorption isotherms, biosorption